Queer : Documents of Contemporary Art. - David J. Getsy (London : Whitechapel, 2016)
Acosta, Niv ; Athey, Ron ; Blake, Nayland ; Blas, Zach ; Bordowitz, Gregg ; Bowery, Leigh ; AA Bronson ; Brooke, Kaucyila ; Burns, A.K. ; Campuzano, Giuseppe ; Conrad, Ryan ; Vaginal davis ; DeGenevieve, Barbara ; Dyke Action Machine! ; Elmgreen & Dragset ; Fani-kayode, Rotimi ; fierce pussy / Fujiwara, Simon ; Fung, Richard ; Gaines, Malik ; Gonzalez-Torres, felix ; Fury, Gran ; Gupta, Sunil ; Hall, Gordon ; K8 Hardy ; Hayes, Sharon ; Hudson ; Hughes, Holly ; Jacoby, Roberto ; Julien, Isaac ; Khaled, Mahmoud ; Leonard, Zoe; Lesbian Avengers ; Liuming, Ma ; Llopis, Maria ; Lord, Catherine ; Lorenz, Renate ; Allyson, Mitchell ; Motta, Carlos ; Moyer, Carrie ; Muholi, Zanele ; Muller, Ulrike ; Ocana ; Olesen, Henrik ; Opie, Catherine ; Hanh Thi Pham ; Radiziszewski, Karol ; Marlon T. Riggs ; Roysdon, Emily ; Sahib, prem ; Assotto saint ; Scott, Braden ; Segade, Alexandro ; Shah, Tejal ; Silman, Amy ; Steiner, L.A. ; Stryker, Susan ; Toxic Titties ; Wu Tsang ; Dahn Vo ; Wojnarowicz, David ; Xing, Yan ; Las Yeguas del Apocalipsis ; Zaatari, Akram ; Zevallos, Sergio
Homoseksualiteit en de kunsten, kunstenaarsteksten
boek